A hierarchical cascade of sleep rhythms supports motor memory and is hijacked by epileptic spikes in human epilepsy - Anirudh Wodeyar; Dhinakaran Chinappen; Hunki Kwon; Wen Shi; R. Mark Richardson; Mark A. Kramer; Catherine J. Chu (Proceedings of the National Academy of Sciences, 2026)
The cross-regional interplay of slow oscillations, spindles, and ripples during sleep is believed to support systems memory consolidation but remains understudied in humans. Using a validated behavioral task and simultaneous intracranial neural recordings from the orbitofrontal cortex, thalamus, and hippocampus in 19 patients with epilepsy, we examined the cross-regional interplay of sleep oscillations (slow oscillations, spindles, and ripples), alongside epileptic spikes, and their role in motor memory consolidation. Orbitofrontal slow oscillations robustly modulate spindle and ripple oscillations within and across regions during sleep. Although most combinations of oscillation rates positively predicted overnight performance change in a motor task, hippocampal ripple rate and coupled hippocampal-orbitofrontal ripple rates were the most reliable predictors across subjects. In contrast, rates of most sleep oscillations coupled to epileptic spikes were negative predictors of overnight motor performance change, with the rate of slow oscillations co-occurring with epileptic spikes the most reliable predictors of negative change across subjects. These findings provide direct evidence of a hierarchical cascade of sleep oscillations in human motor memory processing and reveal that epileptic spikes coupled to sleep oscillations interfere with this process in patients with epilepsy.